PERTANGGUNGJAWABAN PERUSAHAAN TERHADAP KELUARGA PEKERJA YANG MENINGGAL AKIBAT KECELAKAAN KERJA DALAM UU CIPTA KERJA - Surya Insani Kamil (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
This research aims to analyze a company's accountability towards the families of workers who pass away due to work-related accidents within the context of the Omnibus Law. The background of this study underscores the significance of legal protection for workers and their families in the workplace to foster a safe and comfortable working environment. The research method employed is a normative juridical approach, focusing on the analysis of relevant legislation concerning corporate responsibilities. The findings indicate that the Omnibus Law provides a clear legal basis regarding a company's responsibility towards the families of workers involved in work-related accidents. Companies are obligated to provide compensation and rehabilitation to the families of workers who pass away due to work-related accidents in accordance with applicable provisions. In this context, legal protection for laborers becomes paramount in safeguarding the welfare and justice for workers and their families. In conclusion, legal protection for laborers under the Omnibus Law represents a positive step towards enhancing the safety and welfare of workers in the workplace. With clear regulations in place, it is hoped that a safer working environment conducive to worker productivity can be established.